PREPARATION, CHARACTERIZATION, ACTIVITY, DEACTIVATION,AND REGENERATION TESTS OF CoO-MoO/ZnO AND CoO-MoO/ZnO-ACTIVATED ZEOLITE CATALYSTS FOR THE HYDROGENPRODUCTIONFROM FUSEL OIL Preparasi, Karakterisasi, Uji Aktvltas, ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT Preparation,.characterization, activation,deactivation,and regenerationtests of CoO-MoO/ZnOand CoOMoO/ ZnO-ActivatedZeolite (AZ) catalysts for the hydrogen production using .steamreforming of alcohols in fusel oil have been conducted. Both catalysts were prepared by impregnation of Co and Mo onto ZnO or ZnO-AZ powder then followed by calcination at 400°C for 5 h under N2 stream: The BET method and pyridine adsorption were used for catalysts characterization. The study of activation, deactivation, and regeneration of catalysts were conducted by using steam reforming method in the semi flow reactor. The reaction condition were: weight ratio of catalystslfeed = 0.1, temperature: 450°C, duration: 45 min. Thegas product was trapped in a 250 mL vacuumpyrex bottle filled with 50 mL of 4 M NaOH solution and analyzed by GC with TCD system to determine H2existance and HCI titration to determine C02 produced during the process that was dissolved in NaOH solution. The results showed that CoO-. MoO/ZnO-AZ catalyst produced higher gas conversion than CoO-MoO/ZnOcatalyst. However, it had short catalyst lifetime due to its high amount of coke deposited during the process. The regeneration test could enhance the catalyst activity. The gas product consisted of H2(14.70%)and C02 (24.41%). Keywords: fusel oil, steam reforming, deactivation, regeneration, hydrogen production.